Vascular effects of gestational diabetes can be recognized by carotid intima-media thickness: a prospective case-control study - Ercan Kahraman; Metin Senturk; Hulya Aladag; Engin Yıldırım (Medicine Science, 2023)
Gestational diabetes mellitus (GDM) is a systemic disease that has poor maternal and fetal health outcomes. Patients who are diagnosed with GDM are more likely to encounter cardiovascular system diseases during pregnancy and after birth. Carotid intima-media thickness (CIMT) is used as an early indicator of diseases such as coronary artery disease. This study aims to define the effects of hyperglycemia at an early term using CIMT, maternal and fetal doppler flows in patients diagnosed with GDM. The study included 132 pregnant women who had reached the 24th gestational week. (GDM group n=65, Control group n=67) Comparisons were performed between women with similar demographic characteristics who received a 100-gr oral glucose test (OGT) and GDM diagnosis and who did not. The participants' routine hemograms and biochemical tests were done during OGT. Fetal biometrics, amniotic fluid index, uterine artery doppler flow, and bilateral CIMT measurements were performed during the obstetric examinations. Gravida, para, and live birth rates of the GDM group participants were higher than those of the control group (p=0.003, 0.002, 0.002 respectively). The amniotic fluid index was found to be higher in the GDM group (p [Med-Science 2023; 12(1.000): 138-144]